2009
DOI: 10.1248/bpb.32.468
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-fatigue Effects of the Low-Molecular-Weight Fraction of Bonito Extract in Mice

Abstract: Bonito extract (BE), a hot-water extract of bonito muscle, has traditionally been considered as a folk remedy for fatigue. In this study we investigated the effects of BE on physical fatigue. BE was divided into, high, mid, and low-molecular-weight fractions (LMF), to explore the effectiveness of BE compounds. The swimming times to exhaustion of mice administered 0.86 g/kg BE and those administered 0.86 g/kg LMF were significantly longer than those of the vehicle-treated mice in a forced swimming model, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
(33 reference statements)
0
22
0
Order By: Relevance
“…The forced swimming test has been used to evaluate the anti-fatigue effect of medicine, since this apparatus works well for evaluating the endurance capacity of mice and gives a high reproducibility (Nozawa et al, 2009). In this study, the data showed that THSWT significantly prolonged exhaustive swimming time of mice, which indicated that THSWT could elevate the exercise tolerance and possessed an anti-physical fatigue effect.…”
Section: Discussionmentioning
confidence: 62%
“…The forced swimming test has been used to evaluate the anti-fatigue effect of medicine, since this apparatus works well for evaluating the endurance capacity of mice and gives a high reproducibility (Nozawa et al, 2009). In this study, the data showed that THSWT significantly prolonged exhaustive swimming time of mice, which indicated that THSWT could elevate the exercise tolerance and possessed an anti-physical fatigue effect.…”
Section: Discussionmentioning
confidence: 62%
“…DBB has also traditionally been considered a folk remedy for fatigue in the southern part of Japan. In previous works, DBB was confirmed to be effective against fatigue in animal and human studies (22,32). We demonstrated that the daily ingestion of DBB by humans improves mood, especially by alleviating mental fatigue (31), and that it increases performance on a simple calculation task (21).…”
mentioning
confidence: 69%
“…In addition, this forced swimming model shows decreased glycogen in the liver and skeletal muscle, and increased blood lactic acid (19,20). The forced walking model has also been used to evaluate the anti-fatigue effects of various compounds including nutritive and tonic crude drugs (13,21), and bonito extract (14). After forced walking for 3 h, the mice in the present study were found to have a decreased glycogen content in their liver and soleous muscle and an increased level of lactic acid in their blood, indicators of physical fatigue (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The method for applying forced walking has been described in a previous report (13,14). Briefly, forced walking was imposed on 10 mice at room temperature in a cylindrical cage (37-cm diameter), which was rotated on the horizontal axis at 2.0 rpm by an electric motor, giving a walking speed of 2.3 m/min for 3 h. Control mice were placed in a cylindrical cage without rotation.…”
Section: Forced Walking Exposurementioning
confidence: 99%